Effect of Ipomoea aquatica ethanolic extract in streptozotocin (STZ) induced diabetic rats via 1H NMR-based metabolomics approach - Sajak, Azliana Abu bakar; Mediani, Ahmed; Maulidiani, M.; Mohd Dom, Nur Sumirah; Machap, Chandradevan; Hamid, Muhajir; Khatib, Alfi; Abas, Faridah (Elsevier, 2017)
Background: Ipomoea aquatica (locally known as “kangkung”) has previously been reported to have hypoglycemic activities on glucose level in diabetes patients. However, the effect of I. aquatica ethanolic extract on the metabolites in the body has remained unknown. Purpose: Our study provides new insights on the changes of endogenous metabolites causes by I. aquatica ethanolic extract and improves the understanding with regard of therapeutic efficacy and mechanism of I. aquatica ethanolic extract. Methods: By using a combination of 1H nuclear magnetic resonance (NMR) with multivariate analysis (MVDA), the changes of metabolites due to I. aquatica ethanolic extract administration in obese diabetic-induced Sprague Dawley rats (OB+STZ+IA) were identified. Results: The results suggested 19 potential biomarkers with variable importance projections (VIP) above 0.5, which include creatine/creatinine, glucose, creatinine, citrate, carnitine, 2- oxoglutarate, succinate, hippurate, leucine, 1-methylnicotinamice (MNA), taurine, 3- hydroxybutyrate (3-HB), tryptophan, lysine, trigonelline, allantoin, formate, acetoacetate (AcAc) and dimethylamine. From the changes in the metabolites, the affected pathways and aspects of metabolism were identified. Conclusion: I. aquatica ethanolic extract manages to increase metabolite levels such as creatinine/creatine, carnitine, MNA, trigonelline, leucine, lysine, 3-HB and decreases metabolite levels, including glucose and tricarboxylic acid (TCA) intermediates. This implies capabilities of I. aquatica ethanolic extract promoting glycolysis, gut microbiota and nicotinate/nicotinamide metabolism, improving the glomerular filtration rate (GFR) and reducing the β-oxidation rate. However, the administration of I. aquatica ethanolic extract has several drawbacks, such as unimproved changes in amino acid metabolism, especially in reducing branched chain amino acid (BCAA) synthesis pathways and lipid metabolism